Eksplorasi etnomatematika pada Topeng Malangan dengan pendekatan golden ratio - Nada, Siti Akmalia; Asyari, Aisyah Putri (Maliki Interdisciplinary Journal, 2024)
In this study, researchers explored the mathematical elements contained in Malangan Mask Art using the Golden Ratio approach. The approach used in this research is an ethnographic approach, with a qualitative research type. The findings from this research can be integrated into the educational curriculum, especially at the elementary school level. This can help students understand that mathematics is not only limited to textbooks, but is also embedded in everyday life and cultural heritage, thus encouraging students’ interest in mathematics and traditional arts. This article aims to celebrate Indonesia’s rich and diverse cultural heritage, as well as stimulate readers’ curiosity about the deep connections between mathematics and art in various cultures around the world.